Manifestly covariant actions for D = 4 self-dual Yang-Mills and D = 10 super-Yang-Mills - Berkovits, Nathan [UNESP]; Hull, Chris (Springer Nature, 1998)
Using an infinite number of fields, we construct actions for D = 4 self-dual Yang-Mills with manifest Lorentz invariance and for D = 10 super-Yang-Mills with manifest super-Poincaré invariance. These actions are generalizations of the covariant action for the D = 2 chiral boson which was first studied by McClain, Wu, Yu and Wotzasek.
Keywords: Duality in Gauge Field Theories; Extended Supersymmetry; Field Theories in Higher Dimensions; Supersymmetry and Duality